MiR-26a downregulates retinoblastoma in colorectal cancer - Eduardo López-Urrutia; Jossimar Coronel-Hernández; Verónica García-Castillo; Carlos Contreras-Romero; Antonio Martínez-Gutierrez; Diana Estrada-Galicia; Luis Ignacio Terrazas; César López-Camarillo; Hector Maldonado-Martínez; Nadia Jacobo-Herrera; Carlos Pérez-Plasencia (Tumor Biology)
MicroRNAs are non-coding short RNAs that target the 3′ untranslated region of messenger RNAs (mRNAs) and lead to their degradation or to translational repression. Several microRNAs have been designated as oncomirs, owing to their regulating tumor suppressor genes. Interestingly, a few of them have been found to target multiple genes whose simultaneous suppression contributes to the development of a tumoral phenotype. Here, we have showed that miR-26a is overexpressed in colorectal cancer data obtained from TCGA Research Network and in human colon cancer pathological specimens; moreover, an orthotopic in vivo model of colon cancer showed overexpression of miR-26a, while Rb1 expression inversely correlated to miR-26a in TCGA Research Network data, pathological samples, and the in vivo model. Then, by means of luciferase assay, we demonstrated that miR-26a targets the 3′ untranslated region of Rb1 mRNA directly. This is, to our knowledge, the first report of miR-26a targeting Rb1 in colon cancer. The results of this study suggested that miR-26a could serve as a progression biomarker in colorectal cancer. Further validation studies are still needed to confirm our findings.